Is PIN priced risk? - Mohanram, Partha; Rajgopal, Shiva (Journal of Accounting and Economics, 2009)
Several recent papers assume that private information (PIN), proposed by Easley et al. [2002. Is information risk a determinant of asset returns? Journal of Finance 57, 2185–2221; 2004. Factoring information into returns. Working Paper, Cornell University], is a determinant of stock returns. We replicate Easley et al. (2002) and show that while PIN does predict future returns in the sample they analyze, the effect is not robust to alternative specifications and time periods. There is no evidence that PIN factor loadings predict returns or that PIN factor returns reflect future GDP growth. PIN exhibits no association with implied cost of capital derived from analysts’ earnings forecasts. Overall, our findings cast doubt on whether PIN reflects information risk systematically priced by investors.